Local Government Public Services: Measuring the Effect of Attitude of Nagari Apparatus on Public Satisfaction Through the Quality of Public Services - Saputra, Boni; Lanin, Dasman; Magriasti, Lince; Asriati, Afifah; Finna Syolendra, Dwi (KnE Social Sciences, 2024)
The low quality of public services often becomes a public complaint. It even becomes a bad image in the eyes of the public, causing a feeling of public dissatisfaction with the services provided. In service, attitude plays an important role because it is one of the service quality indicators. Good service will be seen from the way and attitude of employees in providing services to the community. This study aims to measure and analyze the influence of the attitude of the Nagari apparatus on public satisfaction through the quality of public services in West Sumatra, Indonesia. An associative quantitative approach was chosen to achieve this goal. The population in this study were people who had dealt with Nagari officials in West Sumatra in public service matters. The sample is determined through two stages, namely: cluster area and quota sampling. A sample of 425 from eight Nagari. Questionnaires validated and tested for reliability were distributed to these respondents. The collected data were then analyzed using Structural Equation Modeling (SEM) Analysis Moment of Structural (AMOS) statistics. The literature study also supports data collection. The results of the research confirm and prove that there is a significant influence of the attitude of the Nagari apparatus on public satisfaction, both directly and through the mediating role of service quality. Thus the results of this study have provided evidence that the model built can be used as an academic rationale to strengthen the theories and models that have been reviewed in this research study. Keywords: attitude apparatus, public satisfaction, public service quality, nagari